OSTEOARTICULAR TUBERCULOSIS OF THE WRIST (Case Report) - Pınar Borman; Hürrem Bodur; Hatice Bodur; Kenan Bayrakçı; Uğur Günel; Selda Seçkin (Archives of Rheumatology, 2002)
Osteoarticular tuberculosis (TB); is an infrequent form of the disease and monoarthritis of the wrist accounts for 1% of all cases of skeletal involvement. Herein, we describe a 71-year-old man presented with progressive right wrist pain and swelling, worsened for the last 9 months. The past medical history was nonspecific and chest x-ray was normal. Laboratory findings were normal except moderate elevation of ESR and CRP levels. He had a strong PPD reaction with 17 mm induration. The radiographs of the wrist illustrated typical features for TB. He had an arthrodesis and the synovial pathology showed granulomatous synovitis. He was started on anti-TB chemotherapy and improved significantly. The differantial diagnosis of this rare condition was discussed with the review of the literature.